Participation of persons deprived of liberty in disaster risk reduction in Philippine jails - Pulangco, Kathleen E.; Sandoval, Louise Antonette T.; Buenaventura, Aizel G.; Carlobos, Kerr John N.; Relampagos, Kate Angela C.; Santiago, Louise Rachel R.; Velasco, Joselle S. (2019)
Incarceration facilities in the Philippines are vulnerable to impacts of natural disasters. The lack of research and policy intervention in this area of prison management and governance, coupled with existing natural hazards and other vulnerabilities, makes persons deprived of
liberty (PDLs) a high risk but low priority minority group in disaster management. This study looks into the situation of PDLs in four selected Philippine jails, namely, city jails of Caloocan, Manila, and Tacloban, and San Mateo Municipal Jail. It presents the recurring patterns and observable behavior of PDLs during disaster events and the level of their
participation in disaster risk reduction management (DRRM) programs. Current prison management policies prohibit PDLs from assisting with the prison administration. However, a gap in policy and practice caused by lack of personnel and resources makes the participation of PDLs necessary. Although further research is needed to identify the underlying mechanisms and relations, findings suggest the advantages of formalizing
PDL participation in DRRM to achieve better operationalization of DRRMrelated activities and attaining orderly prison management.
Keywords: Jails -- Emergency management; Prisoners -- Community involvement -- Emergency management; Prisoners -- Social conditions; Persons Deprived of Liberty (PDL) -- Rehabilitation; Disaster Risk Reduction and Management (DRRM); Bureau of Corrections; Bureau of Jail Management and Penology (BJMP)